Affective and perceptual responses during reduced-exertion high-intensity interval training (REHIT) - Songsorn, P.; Brick, N.; Fitzpatrick, B.; Fitzpatrick, S.; McDermott, G.; McClean, C.; Davison, G. W.; Vollaard, N. B. J.; Metcalfe, R. S. (International Journal of Sport and Exercise Psychology, 2020)
We have previously demonstrated that reduced-exertion high-intensity interval training (REHIT) is a genuinely time-efficient exercise strategy for improving cardiometabolic health. Here, we examined the affective and perceptual responses to REHIT. Eight young men and women (age 21 ± 1 y, BMI 24.9 ± 2.1 m/kg2, VO2max 39 ± 10 ml/kg/min) and 11 men with type 2 diabetes (T2D; age 52 ± 6 y, BMI 29.7 ± 3.1 m/kg2, VO2max 29 ± 5 ml/kg/min) took part in three-arm crossover trials with RPE and affective valence measured during, and enjoyment and exercise preferences measured following either: 1) REHIT (2 × 20-s sprints in a 10-min exercise session), 2) HIIT (10 × 1-min efforts) and 3) 30 min MICT. Furthermore, 19 young men and women (age 25 ± 6 y, BMI 24 ± 4 m/kg2, VO2max 34 ± 8 ml/kg/min) completed a 6-week REHIT intervention with affective valence during an acute REHIT session measured before and after training. Affect decreases (briefly) during REHIT, but recovers rapidly, and the decline is not significantly different when compared to MICT or HIIT in either healthy participants or T2D patients. Young sedentary participants reported similar levels of enjoyment for REHIT, MICT and HIIT, but 7 out of 8 had a preference for REHIT. Conversely, T2D patients tended to report lower levels of enjoyment with REHIT compared with MICT. The decrease in affective valence observed during an acute REHIT session was significantly attenuated following training. We conclude that affective and perceptual responses to REHIT are no more negative compared to those associated with MICT or HIIT, refuting claims that supramaximal sprint interval training protocols are associated with inherent negative responses.